Topical and Oral Therapies for Childhood Atopic Dermatitis and Plaque Psoriasis - Frantz, Travis (Children (Basel), 2019)
Background: Treatment of atopic dermatitis and psoriasis in children is difficult due to lack of standardized treatment guidelines and few FDA-approved treatment options. Treatments approved for adults may be used off-label in pediatric patients. Objective: This review evaluates the topical and oral treatment options available, including off-label uses, and provides a basic therapeutic guideline for pediatric atopic dermatitis and psoriasis. Methods: A PubMed review of topical and systemic treatments for pediatric psoriasis and atopic dermatitis with information regarding age, efficacy, dosing, contra-indications, adverse events, and off-label treatments. Results: The search identified seven topical and five systemic treatments that are routinely employed to treat pediatric atopic dermatitis and psoriasis. Limitations: Standardized guidelines regarding treatment choice, dosing, and long-term safety are scarce. Reviews may be subject to ascertainment bias. Conclusions: Current treatment guidelines are based on clinical experience and expert advice with few treatments officially approved for atopic dermatitis and psoriasis in children.